Quality changes during processing and storage of dehydrated Halymenia durvillaei - Palacios Joy Ann G.; Rumbaoa, Rowena Grace O. (2007)
ABSTRACT The study was conducted to determine the changes in the quality-related properties of dehydrated Halymenia during processing and storage. Oven-drying resulted to a relatively minimum color changes as compared to freeze-drying. Only the Hunterlab b parameter was significantly (Pr>F=0.04) affected by oven-drying. The decrease in the b parameter can be attributed to the effect of high temperature used in the dehydration process. The storage study of dehydrated Halymenia for 28 days at 55°C showed that Hunterlab L (Pr>F=0.0001), a (Pr>F=0.0010) and b (Pr>F=0.0001) values were affected by the dehydration process and storage time. Generally, the redness parameter of Halymenia was increased by freeze-drying and unaffected by oven-drying. The sensory evaluation data revealed that the consumer acceptance scores were not significantly different (Pvalue>0.05) from Day 0 to Day 28 indicating that changes detected by the Hunterlab chromameter were not significant enough to affect the consumer acceptance of the products. The oven-dried Halymenia were significantly (Pr>F=0.0001) more acceptable as compared to the freeze-dried Halymenia. The microbial loads of both freeze-dried and oven-dried Halymenia are within acceptable range making the products safe for consumption.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Seaweeds -- Preservation; Seaweeds